Analysis of iron levels in the mucosal tissue and serum of oral submucous fibrosis patients - Basavaraj N Kallalli; Pavan K Gujjar; Kamala Rawson; Sudhir Bhalerao; Treville Pereira; Jyoti Zingade (Wolters Kluwer Medknow Publications, 2016)
Introduction: Oral submucous fibrosis (OSMF), being a chronic insidious oral mucosal condition, affects most parts of the oral cavity and has a high malignant transformation rate, which is triggered by areca nut chewing, nutritional deficiencies, immunologic processes, and genetic predisposition. Aims and Objectives: The objective of the present study was to evaluate the levels of iron, as a trace element of patients with OSMF, and its association with areca nut and betel quid chewing. Materials and Methods: The study sample comprised 30 patients who were clinically diagnosed with OSMF and 10 healthy controls. OSMF patients were categorized by clinical staging. Tissue and serum estimation of iron levels was done using Vitros 250 photometry. Results: The levels of tissue and serum iron was significantly decreased in OSMF patients when compared to controls, which was statistically significant. Conclusion: Most of the patients with OSMF chewed gutkha, as compared to the transitional form of pan masala. The betel quid and areca nut chewing habits are associated with the disease state, which may play a role in altering the tissue and serum iron levels.